Specific features of memory functioning during traumatic events - Lahutina, Софія; Subbota, Спартак (Psychosomatic Medicine and General Practice, 2020)
Introduction. Throughout life, people experience potentially traumatic events that can lead to psychopathological manifestations and psychological distress, including trauma-related anxiety disorders. During the first month after exposure to a traumatic event, an acute stress reaction (ASR) may occur, which may then transform into post-traumatic stress disorder (PTSD). PTSD is a heavy burden on the health care system of any country, negatively affects the physical and psychological well-being of a person, and, of course, impairs the social functioning of the victim. Intrusive memories are one of the main symptoms of PTSD, they are anxious and obsessive, based on images of a traumatic event and are emotionally colored. PTSD models have shown that it is intrusive memories that can activate other PTSD symptoms. Based on this, it can be concluded that interventions aimed at overcoming intrusive memories will have a positive effect on other symptoms of PTSD. Goal. Generalization of current data on the functioning of memory mechanisms underlying the occurrence of post-traumatic stress symptoms, systematization and comparison of theories of traumatic memory in recent years, and effective interventions that can be used to prevent PTSD. Materials and methods. Qualitative and quantitative content analysis of English-language literature for the last 15 years was conducted on the main approaches to explaining the functioning of memory during traumatic events, the formation of traumatic memories. The search was performed using databases Pubmed, CrossRef. Conclusions. This review summarizes the main theories that explain the occurrence of traumatic memories after a stressful event, the peculiarities of memory functioning and information processing. The ability to process traumatic memory is the basis for favorable post-traumatic adaptation. It is extremely important to develop behavioral interventions that can be mechanically controlled, low intensity and will be provided by non-specialists, will be easy to use, which will help to ensure their widespread use and accessibility.